2018
DOI: 10.1111/clr.13277
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the survival and complication rates of zirconia‐ceramic and metal‐ceramic multiple‐unit fixed dental prostheses

Abstract: Objectives:The aim of the present review was to compare the outcomes, that is, survival and complication rates of zirconia-ceramic and/or monolithic zirconia implant-supported fixed dental prostheses (FDPs) with metal-ceramic FDPs. Materials and Methods: An electronic MEDLINE search complemented by manual searching was conducted to identify randomized controlled clinical trials, prospective cohort studies and retrospective case series on implant-supported FDPs with a mean follow-up of at least 3 years. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
3
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 31 publications
8
164
3
13
Order By: Relevance
“…In a similar manner, Pieralli et al 208 207 this study demonstrated a high incidence of chipping of the veneering material and pointed out that clinical evidence descriptive of monolithic zirconia restorations is lacking.…”
Section: Implant Dentistrysupporting
confidence: 52%
“…In a similar manner, Pieralli et al 208 207 this study demonstrated a high incidence of chipping of the veneering material and pointed out that clinical evidence descriptive of monolithic zirconia restorations is lacking.…”
Section: Implant Dentistrysupporting
confidence: 52%
“…Therefore, the search strategy of our group has changed to apply a very open and unrestricted title search, avoiding limitations and filters in order to be as inclusive as possible on the title level. Additionally, meticulous hand‐searching of all reference lists of previous reviews and all included full‐text papers of the present systematic review helped locating the included studies of the present and a parallel review addressing multi‐unit implant supported fixed dental prostheses (Sailer et al., ; ITI CC SR).…”
Section: Discussionmentioning
confidence: 99%
“…In the final article selection phase, data were divided into implant‐supported SCs, for the present systematic review and fixed dental prostheses (FDPs) for the review by Sailer et al. (). Both reviews were prepared in the context of the ITI Consensus Conference 2018.…”
Section: Methodsmentioning
confidence: 99%
“…There have been few papers reporting the long-term clinical results of fixed implant-supported monolithic Y-TZP restorations for periods of over five years [57][58][59][60][61][62][63][64]. The five-year survival rate is estimated to be over 90% in complete-arch fixed implant-supported monolithic Y-TZP prostheses [57,64].…”
Section: Zirconiamentioning
confidence: 99%
“…The five-year survival rate is estimated to be over 90% in complete-arch fixed implant-supported monolithic Y-TZP prostheses [57,64]. There appear to be no studies on single or multiple-unit fixed implant-supported monolithic Y-TZP dental prostheses with a mean follow-up period of at least 3 years [62,63]. As SM-based monolithic Y-TZP restorations are being used in clinics globally, randomized controlled trials and other prospective clinical studies will be reported and published in the near future.…”
Section: Zirconiamentioning
confidence: 99%